Mortality after hip resurfacing versus total hip arthroplasty in young patients: a single surgeon experience - Brooks, Peter J.; Samuel, Linsen T.; Levin, Jay M.; Sultan, Assem A.; Khlopas, Anton; Brigati, David; Ng, Mitchell; Greenwald, A. Seth; Mont, Michael A. (Annals of Translational Medicine; Vol 7, No 4 (February 27, 2019): Annals of Translational Medicine (Focus on “Lower Extremity Arthroplasty”), 2019)
Background: The aims of this study were to investigate the following questions: (I) what are the mortality rates in patients age 55 years and younger who underwent a hip resurfacing arthroplasty (HRA) versus a standard total hip arthroplasty (THA)? (II) is the type of operation independently associated with mortality? Methods: The database of a single high-volume surgeon was reviewed for patient’s age 55 years and younger who underwent a hip arthroplasty between 2002 and 2010. This yielded 505 HRA patients and 124 THA patients. Chi-square analysis was performed to identify a 5-year mortality rate difference between the two cohorts. Multivariable Cox-Regression analyses were used to determine whether the type of operation was independently associated with mortality. Results: There were 8 mortalities (1.6%) in the HRA cohort and 11 (8.9%) in the THA cohort, a statistically significant difference (P